Nocturnal enuresis among kindergarten-aged children in Kubang Kerian, Kelantan - Mustapha, Nor Zalikha Muhamad (Universiti Sains Malaysia, 2014)
Nocturnal enuresis (NE) is the second most chronic health problem in children and it also can lead to socially disruptive and stressful condition. The aim of the present study was to identify the prevalence, associated risk factors, parents strategies to overcome NE and parents health seeking behavior for child’s NE. A cross sectional survey study was conducted on 70 children aged between five to six years old at four kindergarten in Kubang Kerian, Kelantan. Participant in this study was selected through simple random sampling method. The association between selected socio-demographic characteristics (age. gender, and number of siblings) and Nocturnal Enuresis were analyzed using chi-square test and STATA. The association between school performance (social, academic and physical) and Nocturnal Enuresis also was tested. The overall prevalence of Nocturnal Enuresis was 47.1%. The associated risk factors for Nocturnal Enuresis were positive family history, problem during birth, hyperactivity of the child, urinate in pants during a day. constipation and urinary tract infection. Most 45.7% of parents had woke their child up to urinate as a strategy to overcome NE. All parents had not seek treatment for child with NE. A significant association was found between number of siblings and nocturnal enuresis (p= 0.024). A significant association was also indicated between school performance (social, academic and physical) and nocturnal enuresis (p<0.05). Identification of children at risk is an essential step before choosing the individualized management for child's NE. The parents also must seek appropriate treatment from health professional and applied the suitable strategies to overcome child’s NE.